Another place : identity, space, and transcultural signification in Goli Taraqqi's fiction - Ghardashkhani, Goulia. (Iran Studies, 2018)
In Another Place: Identity, Space, and Transcultural Signification in Goli Taraqqi's Fiction , Goulia Ghardashkhani examines the narrative process of the struggle for identification in the short stories of one of the well-established figures of Iranian contemporary prose literature. Goli Taraqqi's narratives of displacement and emigration are approached through a theoretical lens that foregrounds the significance of space and the role of retrospective self-narration in acts of cultural representation. Ghardashkhani studies Taraqqi's autobiographical narratives with an emphasis on the unstable meanings of homeland and Farang (a culturally constructed term signifying the West) and, thereby, accounts for Taraqqi's ironical style of narration in her memories of homeland recollected in exile.